Foreign exchange market contagion: evidence of DCC and DECO Multivariate GARCH Models - Si Mohammed, Kamel (Université de M'sila, 2016)
The goal of this study is to measure contagion phenomenon between foreign exchange markets during Subprime crisis & Euro-Zone crisis using daily data from 03/01/2005 to 03/09/2015 for twenty selected countries. In our analysis, we use the FMI classification of exchange rate arrangements for each estimation period. We also separated an estimation period in two period’s crises. estimate into two crises periods. Firstly, the US Subprime crisis period that covers the period from 17/07/2007 through 31/08/2009 (See Dungey, 2009, Celik, 2012), and secondly, the period span of the Euro-zone crisis that goes from 19.11.2009 to 31.12.2012 (See Wasim. A et al 2013).The model we use in this study is a Dynamic Equicorrelation GARCH model of Engle and Kelly (2012) and DCCGARCH model of Engle (2002). In summary, we conclude that all exchange rates returns series are influenced by the contagion effects come from USA and euro area over 2007-2012 periods. Moreover, we observe that the mean Dynamic conditional correlation of the multivariate GARCH increase in financial and Euro zone crises compared to the pre-crisis period. In addition to that, we conclude that persistent volatility has been high in countries adopting free floating exchange rates compare the countries they supported managed floaters, hard and soft begs exchange rate regimes.
Keywords: Contagion, Subprime and Eurozone Crises, DCC-GARCH, DECO-GARCH, Exchange Rate Regimes.